Climate change vulnerability and coping mechanisms among farming communities in Northern Ghana - Nti, Frank Kyekyeku (Kansas State University, 2012)
This study examines the effect of extreme climatic conditions (drought, flood, and bushfires) on the livelihood of households in the Bawku West district of Ghana. The research identified the mechanisms with which households cope in such situations, and analyzed factors influencing the adoption of coping strategies for flood, coping strategies for drought, and coping strategies for bushfires. Data for the study were collected in selected villages across the district in the aftermath of the 2007/2008 extreme climatic events (a prolonged drought period followed by an erratic rainfall). A binary logit regression (BLR) model was then specified to estimate factors that influence the adoption of a given coping mechanisms. Results from the BLR model indicate that literacy level, membership with an FBO, household income, and location of households had positive and significant impacts on adaptation to drought. Similarly, source of seeds for planting, membership with an FBO, household income, and farm size had positive significant influence on adaptation to flood. Adaption to bushfire was positively influenced by radio ownership, seed source and income. The main effect of these climatic extreme events on households included destruction of crops, livestock and buildings; food and water shortage; poor yield or harvest and limited fields for livestock grazing. Therefore, government policies should be geared towards creating revenue generating channels and in strengthening institutions that provide access to farm credit, readily available improve seeds and extension. Additionally, policies that expedite information dissemination through radio and other public media will enhance households’ adaptive capacity.
Keywords: Climatic Conditions; Coping; Binary Logit; Drought; Flood; Bushfires; Economics, Agricultural (0503); Environmental economics (0438)